Optimization of cut surface quality during CNC Plasma Arc Cutting process - Tsiolikas, Aristidis; Kechagias, John; Salonitis, Konstantinos; Mastorakis, Nikos (North Atlantic University Union, 2016)
Optimization of cut surface quality during CNC plasma-arc cutting (PAC) of mild steel plates is presented. Using design of experiments (DOE) the optimum process parameters are estimated. The process parameters tested include cutting speed, cutting height and arc voltage. Analysis of means (ANOM) and analysis of variances (ANOVA) were used in order for the effect of each parameter on the surface quality to be assessed.
Keywords: Plasma-arc cutting; Carbon steel plates; Design of experiments; Surface roughness